(untitled) - Lefrancois, Guy R. (Belmont, CA, 1995)
As in previous editions, this book approaches the study of child development from an inside/outside perspective, looking at children from an abstract or research-based point of view as well as from a personal or experiential perspective. The whole child is addressed at each stage of development in a chronological format with each stage presenting physical, cognitive, social, and emotional facets of the child. Strong coverage of research, theory, and issues in developmental psychology is augmented with examples to show their implications to students.
Keywords: Phát triển của trẻ,Child development